Extra sex combs buffers sleep-related stresses through regulating Heat shock proteins. - Zhao, X.; Li, Y.; Zhao, Z.; Du, J. (FASEB Journal (Federation of American Societies for Experimental Biology), 2021)
The impact of global warming on the life of the earth is increasingly concerned. Previous studies indicated that temperature changes have a serious impact on insect sleep. Sleep is critical for animals as it has many important physiological functions. It is of great significance to study the regulation mechanism of temperature-induced sleep changes for understanding the impact of global warming on insects. More importantly, understanding how these pressures regulate sleep can provide insights into improving sleep. In this study, we found that extra sex combs (ESC) are a regulatory factor in this process. Our data showed that ESC was an upstream negative regulatory factor of Heat shock proteins (Hsps), and it could regulate sleep in mushroom and ellipsoid of Drosophila. ESC mutation exaggerates the sleep change caused by temperature, while buffering the shortening of life caused by sleep deprivation. These phenotypes can be rescued by Hsps mutants. Therefore, we concluded that the ESC buffers sleep-related stresses through regulating Hsps.